PENGEMBANGAN E-MODUL MATEMATIKA PADA MATERI BANGUN DATAR KELAS III SDN DLAMBAH DAJAH 2 - Nur Toyyibah; Umi Hanik (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This study aims to develop teaching modules in the form of Electronic Modules on flat building materials that are valid, effective and interesting to use in class III SDN Dlambah Dajah 2. This development research uses the 4D model. The data collection techniques used are observation, interviews, questionnaires, and tests. Based on the results of the validation of learning media experts, subject matter, language and learning design obtained an average percentage of the overall validity of 87.5% with a very valid category. The effectiveness of the product is seen from teacher activity observations of 92% with a very effective category, observation of student activity of 91.6% with a very effective category, the results of student learning tests obtained an average of 100% so that it is declared effective. The results of attractiveness based on the average teacher response questionnaire obtained a percentage of 92.5% and the student response questionnaire obtained a percentage of 89.75% in the very interesting category. The results showed that the Mathematics E-Module learning media was very valid, effective, and effective to use in learning.